PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI KLASIFIKASI MAKHLUK HIDUP DI SMP NEGERI 3 MEDAN - Rizki Pratama; Yusuf Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning instructional model on students’ learning outcomes in the topic of living things classification in Grade VII junior high school. This research is a quasi-experimental study with a pretest-posttest control group design, conducted in the even semester of the 2025/2026 academic year at SMP Negeri 3 Medan. The population in this study consisted of all Grade VII students, comprising eleven classes. The sample was selected using cluster random sampling technique, with class VII-I assigned as the experimental group, which was taught using the Problem Based Learning model, and class VII-H assigned as the control group, which was taught using the Direct Instruction model. The data collection instrument was a validated multiple-choice test consisting of 20 questions measuring learning outcomes. Data were obtained through pre-test and post-test and analyzed using a one-tailed t-test. The results showed that the mean pre-test and post-test scores in the experimental class were 40.94 and 79.69, respectively. Meanwhile, the control class obtained mean pre-test and post-test scores of 41.56 and 75.16, respectively. The hypothesis testing results showed that tcount > ttable (1.92 > 1.670), so H0 was rejected and Ha was accepted. Thus, it can be concluded that there is a significant effect of the implementation of the Problem Based Learning model on students’ learning outcomes in the topic of living things classification for Grade VII students at SMP Negeri 3 Medan.